Communication tools for Improved knowledge sharing in Rainwater management: Case study of Nile Basin Development Challenge Project. - Damtew, Elias (2012)
The technical, economic, and ecological aspects of rainwater management are interlinked and spatially bounded. Developing, scaling-out, and targeting rainwater management innovations as adaptive strategies to upgrade rainfed agriculture are therefore preferably best approached through integrated innovations and recommendation domains as a paradigm. At the level of scenario development, the integrated innova-tions paradigm helps to understand and address integrity between technical, economic, and ecological issues that affect technology adoption, impact, and sustained use. At the level of scaling-out and targeting, recom-mendation domains provide the spatial dimension that embraces the economic, institutional, biophysical,and agro-ecological conditions in which integrated rainwater management innovations can be accommodat-ed to address heterogeneity. This paper reviews Ethiopia's experience in rainwater management (adoption,performance, and impact) to get insights about the proposed paradigm and the factors entering the para-digm. The endings suggest that integrated innovations and the conditions of success embraced in a recom-mendation domain provide the necessary and sufficient conditions for a successful rainwater management intervention at a landscape level.